Marshall McLuhan : cosmic media - Marchessault, Janine (Core Cultural Theorists series., 2005)
Why is McLuhan important? What use can we make of his approach to the media today? In this insightful critical introduction, McLuhan's contribution is carefully explained and his reputation reassessed. The book: explains McLuhan's key ideas; engages with critical issues in media and contemporary art; demonstrates the relevance of his work for students of media and communications; addresses his methodological contribution; revises our understanding of his place in the history of ideas.